3 - The Determination and Analysis of Constraints in Resource Use Efficiency in Multiple Cropping Systems by Small-Holder Farmers in Ebonyi State, Nigeria: DOI: 10.4314/ad.v29i3.22199 - Awoke , Michael U.; Okorji , Eugene C. (Africa Development, 2004)
The constraints militating against the smallholder fanners in multiple-cropping system in Ebonyi State, Nigeria were analysed. A multi-stage sampling technique was adopted to sample and administer questionnaires to 240 smallholder multiple croppers. Data were collected and analysed using descriptive statistics. High lease charges (45 percent), problems of land fragmentation (35 percent), the low fertility of the land (78 percent), the distance of cultivable land (52 percent) and sex discrimination (100 percent) were constraints militating against the efficiency of land use. The constraints against efficient labour use were the high cost of labour, emigration, sex discrimination, and other competing labour uses, which constituted 23 percent, 22 percent, 19 percent and 14 percent respectively. Responses regarding constraints against capital use referred to the non-availability of improved varieties of yam and cocoyam (29 percent), the high cost of modern inputs (36 percent), the lack of adequate finance (33 percent), and the lack of collaterals (22 percent). The study confirmed that multiple-cropping system would have been more efficient if these constraints were reduced or eradicated. Effective extension services as well as efficient policy formulation and implementation by government are therefore recommended.